2009
DOI: 10.1007/s11746-009-1512-2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Temperature Dependent Viscosity for Unaltered Waste Soybean Oil Blended with Petroleum Fuels

Abstract: Using vegetable oil based alternative fuels for diesel engines has grown in interest over recent years due to the rising cost of petroleum products and instability in the energy marketplace. One of the major hurdles to overcome in using vegetable oil as a diesel fuel is high viscosity. Here, we experimentally determine the viscosity of unaltered waste soybean oil (WSO) blended with petroleum fuels. Three blend viscosity models Arrhenius, Wright, and the ASTM D7152-05 Standard were evaluated for viscosity predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Gutti et al measured kinematic viscosity for quality test of the biodiesel fuels produced from Balanite aegyptiaca seed oil by catalyzed (1.5 % KOH) transesterification with methanol at 333 K. The kinematic viscosity was measured using the ASTM D445 method at temperature of 313.15 K. Maksimuka measured the viscosity of FAEEs of rapeseed oil in the temperature range from (293 to 353) K using commercial capillary viscometer with uncertainty of 0.01 mm 2 ·s –1 . The viscosity of vegetable oils and diesel oil blends have been measured in several publications (see, for example refs and ).…”
Section: Review Of the Measurements And Prediction Models For The Vis...mentioning
confidence: 99%
See 1 more Smart Citation
“…Gutti et al measured kinematic viscosity for quality test of the biodiesel fuels produced from Balanite aegyptiaca seed oil by catalyzed (1.5 % KOH) transesterification with methanol at 333 K. The kinematic viscosity was measured using the ASTM D445 method at temperature of 313.15 K. Maksimuka measured the viscosity of FAEEs of rapeseed oil in the temperature range from (293 to 353) K using commercial capillary viscometer with uncertainty of 0.01 mm 2 ·s –1 . The viscosity of vegetable oils and diesel oil blends have been measured in several publications (see, for example refs and ).…”
Section: Review Of the Measurements And Prediction Models For The Vis...mentioning
confidence: 99%
“…The revised Yuan’s model is the original Yuan’s model in which the VTF parameters were refitted to the new experimental viscosity data. , The model proposed by Freitas et al was compared with the models by Ceriani et al, Krisnangkura et al, and Yuan et al The average deviations between the same experimental viscosity data and the predicted values from models ,,, are 4.65 %, 5.34 %, 8.07 %, and 7.25 %, respectively. Wagner et al showed that the Arrhenius method using volume fractions most accurately (within 2.31%) predicts the viscosity of binary blends of WSO.…”
Section: Review Of the Measurements And Prediction Models For The Vis...mentioning
confidence: 99%
“…It can be blended with diesel fuel to be used in conventional engines and is able to reduce the carbon dioxide emissions by 78% . Although most commercially available biodiesel is still between 5 and 20% biodiesel blended with petroleum diesel because of the higher prices of feedstocks for biodiesel production, the tendency of increasing production is expected to continue in the coming decades with the development and growth of nonfood feedstocks …”
Section: Introductionmentioning
confidence: 99%
“…However, their use requires a heated fuel-supply system to lower the viscosity to allow proper flow through the fuel system, fuel injector-spray patterns, and atomization of the fuel. An alternate approach to solving the viscosity issue is to blend vegetable oil with petroleum fuels . There have been a number of reports and evidence indicating good engine power and acceptable emissions with diesel engines operating on SVO blended with petroleum diesel .…”
mentioning
confidence: 99%